A TRANSITION FROM IPV4 TO IPV6 THROUGH THE DEVELOPMENT OF IPV6 TESTBED - Roestam, Rusdianto (TEKNOINFO, 2007)
IPv6 as a successor cannot be implemented directly in the network for totally replacing IPv4 because of IPv4 worldwide deployment for more than two decades. The choice is to make IPv6 be co-exist with IPv4 for certain time. Ipv4/lPv6 dual-stack is configured in a tunnel to support both protocols. This paper will describe how IPv6 testbed is developed and tested. Basic Network Services (BNS) is also implemented on the network to demonstrate the functionality of the IPv6 protocol. The development activities can be a